2002
DOI: 10.1002/1521-396x(200212)194:2<494::aid-pssa494>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

GaN Boule Growth: A Pathway to GaN Wafers with Improved Material Quality

Abstract: Hydride vapor phase epitaxial growth of GaN boules was investigated. GaN boules were formed at growth rates in excess of 100 μm/h, resulting in boules as long as 5 mm in the c‐axis direction. The boules were sliced into wafer blanks. Lapping, polishing and chemical‐mechanical polishing was employed to produce wafers with a slightly stepped surface. Dislocations were decorated with hot phosphoric acid etching so that the change in defect density with boule length might be studied. Etch pit density correlated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…The nominal indium mole fraction in the InGaN MQWs was B0. 10. The microstrutural properties of the LEDs were characterized using atomic force microscopy (AFM) and transmission electron microscopy (TEM).…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…The nominal indium mole fraction in the InGaN MQWs was B0. 10. The microstrutural properties of the LEDs were characterized using atomic force microscopy (AFM) and transmission electron microscopy (TEM).…”
Section: Methodsmentioning
confidence: 90%
“…Large (up to 2 00 ) free-standing crack-free GaN substrates are now commercially available [10,11]. Yasan et al [3] demonstrated 340 nm AlGaN LEDs on a HVPE grown GaN substrate, and the device produced an output power one order of magnitude higher than similar LEDs grown on sapphire.…”
Section: Introductionmentioning
confidence: 87%
“…The TD density could be decreased to around 10 4 -10 6 cm -2 with increasing of GaN thickness [88]. In this vapor-phase growth technique, gallium chloride (GaCl) will be first synthesized by the reaction between metallic gallium and hydrogen chloride (HCl).…”
Section: The Aspect Of Gan Epitaxy Substrate Selectionmentioning
confidence: 99%
“…2(a)] using such a buffer approach [49], [50]. Two-inch boule growth ranging from 2.5 and 3.5 mm up to 10 mm has been reported also by ATMI Inc, [51], Ferdinand-Braun-Institute [52], and Kyma Technologies, Inc. [ Fig. 2(b)] [53], [54], respectively.…”
Section: B Boule Growth Developmentmentioning
confidence: 99%